1989
DOI: 10.1073/pnas.86.11.4092
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding of victorin to a 100-kDa protein from oats

Abstract: Susceptibility of oats to victoria blight, caused by the fungus Cochliobolus victoriae, and sensitivity to the host-specific toxin victorin, produced by the fungus, are controlled by the dominant allele at the Vb locus. It has been postulated that the Vb locus encodes a toxin receptor, although direct evidence for such a receptor is not available. Our recent studies on structure-activity relationships of the toxin established a methodology for producing '25I-labeled victorin. Electrophoretic analysis of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 13 publications
2
54
0
1
Order By: Relevance
“…However, considering that treatment with Zwittergent 3-12 extracts about 50% of the binding activity, one would expect the 70-kDa band to account for at least 50"h of the specific ' ' ' 1 labeling in membranes, which is not the Besides providing clear identification of a membrane polypeptide with high affinity and specificity for a fungal signal molecule which triggers a plant defense response, this is one of the few reports for plant cells where a putative receptor for an external signal or effector has been identified by photoaffinity labeling and/or affinity chromatography. Previous reports have involved a binding protein for the growth regulator indoleacetic acid (Hicks et al, 1989a, b) and for the fungal phytotoxins fusicoccin (de Boer et al, 1989;Feyerabend and Weiler, 1989;Oecking and Weiler, 1991) and victorin (Wolpert and Macko, 1989). The mechanisms by which these proteins, including the heptaglucoside-binding protein, are linked to signal transduction in plant cells still have to be clarified before a clear receptor function can be assigned to them.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering that treatment with Zwittergent 3-12 extracts about 50% of the binding activity, one would expect the 70-kDa band to account for at least 50"h of the specific ' ' ' 1 labeling in membranes, which is not the Besides providing clear identification of a membrane polypeptide with high affinity and specificity for a fungal signal molecule which triggers a plant defense response, this is one of the few reports for plant cells where a putative receptor for an external signal or effector has been identified by photoaffinity labeling and/or affinity chromatography. Previous reports have involved a binding protein for the growth regulator indoleacetic acid (Hicks et al, 1989a, b) and for the fungal phytotoxins fusicoccin (de Boer et al, 1989;Feyerabend and Weiler, 1989;Oecking and Weiler, 1991) and victorin (Wolpert and Macko, 1989). The mechanisms by which these proteins, including the heptaglucoside-binding protein, are linked to signal transduction in plant cells still have to be clarified before a clear receptor function can be assigned to them.…”
Section: Discussionmentioning
confidence: 99%
“…It is known to increase the cell membrane permeability of susceptible oat plants (Avena sativa), containing the Victoria (Vb) gene, which also encodes for resistance (Pc-2) against Puccinia coronata (16,31). Changes in membrane permeability were most typically expressed in irreversible K+ efflux from leaves, roots, and leaf protoplasts (2,12,18,24,30).…”
Section: Introductionmentioning
confidence: 99%
“…Whatever the explanation for the differences in the binding specificity seen in vivo and in vitro, the in vivo binding results strongly hinted that the 100-kD protein might be a biologically important target for victorin (a 15-kD VBP, by contrast, was found to bind victorin in both resistant and susceptible plants, both in vivo and in vitro; Wolpert and Macko, 1989). Wolpert et al (1994) therefore obtained and sequenced acDNA for the 100-kD VBP and found that it encodes the P-protein component of the GDC.…”
Section: In Thls Issuementioning
confidence: 99%
“…Many years of biochemical studies have shown that victorin binds strongly (and probably covalently) to severa1 oat proteins (e.g., Wolpert and Macko, 1989), but these analyses did not reveal how victorin might affect the metabolism of cells from susceptible plants. On pages 463-471 of this issue, Navarre and Wolpert now demonstrate a possible basis for victorin toxicity: it acts as a potent inhibitor of the glycine decarboxylase complex (GDC), a multienzyme complex found in the mitochondrial matrix.…”
mentioning
confidence: 99%
See 1 more Smart Citation